Evaluasi Kesiapan dan Strategi Akselerasi Adopsi Smart Green Technology pada UMKM Manufaktur di Kota Banjarmasin - Wulandari, Dyah; Maulana, Yassyir; Oscar, Agus Wiramsya; Putri, Sonia (SENTRI: Jurnal Riset Ilmiah, 2026)
The adoption of Smart Green Technology (SGT) is crucial for enhancing the competitiveness of manufacturing MSMEs (Micro, Small, and Medium Enterprises) to support Indonesia's green economic transformation and industrial downstreaming. However, the readiness level of these manufacturing MSMEs, particularly within Banjarmasin City, has never been comprehensively measured. This study aims to analyze SGT adoption readiness using the Technology Organization Environment (TOE) framework and formulate acceleration strategies. An explanatory sequential mixed-methods approach was employed, surveying 100 manufacturing MSMEs across five districts in Banjarmasin City, followed by structured stakeholder interviews. Principal Component Analysis (PCA) constructed the SGT Readiness Index, while qualitative data informed the acceleration strategies. Results showed eight indicators met factor analysis requirements, with a KMO value of 0.628 and a significant Bartlett's Test (p<0.001). PCA generated three main factors explaining 56.6% of the data variance: organizational readiness, operational and financial aspects, and technical and human resources. Based on the Readiness Index, North Banjarmasin MSMEs showed the highest readiness level (59.78), whereas Central Banjarmasin had the lowest (40.36). Additionally, textile and craft MSMEs, alongside businesses operating for 5-10 years, demonstrated higher readiness compared to the food and beverage sector. These findings indicate that organizational factors are the primary determinants of successful SGT adoption. Therefore, acceleration strategies must focus on strengthening organizational capacity, providing green financing, improving human resource competencies, and fostering government policy support to develop green industry ecosystems.